2012
DOI: 10.1016/j.jegh.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

On the reliability of self-reported health: Evidence from Albanian data☆

Abstract: This paper investigates the reliability of self-assessed measures of health using panel data collected in Albania by the World Bank in 2002, 2003 and 2004 through the Living Standard Measurement Study project. As the survey includes questions on a self-assessed measure of health and on more objective health problems, both types of information are combined with a view to understanding how respondents change their answers to the self-reported measures over time. Estimates from random effects ordered Probit model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…This was captured by self-perceived health status, rated on a five-point scale (excellent, very good, good, fair and poor). We chose this measure as studies have considered it to be in accordance with the health records of health providers, as well as a valid health status indicator for population health monitoring and a reliable predictor for GP and hospital use among older adults (Bremer et al 2018, Miilunpalo et al 1997, Ritter et al 2001, Vaillant and Wolff 2012Weinberger et al 1986). It also has an advantage in terms of capturing the biological, psychological and social dimensions of health, as opposed to only the medical diagnosis (Miilunpalo et al 1997).…”
Section: Covariatesmentioning
confidence: 99%
“…This was captured by self-perceived health status, rated on a five-point scale (excellent, very good, good, fair and poor). We chose this measure as studies have considered it to be in accordance with the health records of health providers, as well as a valid health status indicator for population health monitoring and a reliable predictor for GP and hospital use among older adults (Bremer et al 2018, Miilunpalo et al 1997, Ritter et al 2001, Vaillant and Wolff 2012Weinberger et al 1986). It also has an advantage in terms of capturing the biological, psychological and social dimensions of health, as opposed to only the medical diagnosis (Miilunpalo et al 1997).…”
Section: Covariatesmentioning
confidence: 99%
“…Self-reported health status is one of the commonly used predictors of morbidity and mortality among populations. 26 It was assessed through the question "How do you rate your general health?" with the options "excellent, " "very good, " "good, " "average, " and "poor. "…”
Section: Outcome Measurementmentioning
confidence: 99%
“…For the analysis, the answers were classified into three groups as "good" (including excellent, very good, and good), "fair, " and "poor. " 26,27 History of having a chronic disease was assessed with a question "Have you ever been diagnosed by a doctor with one or more chronic illnesses?" with the answer options "Yes" and "No. "…”
Section: Outcome Measurementmentioning
confidence: 99%
“…In this paper, we use all parental health measures available in our dataset. These measures while being subjective 7 are commonly used in empirical research using survey data because they are found to be a strong predictor of true physical or mental health (Contoyannis, Jones, & Rice, 2004;Doiron, Fiebig, Johar, & Suziedelyte, 2015;Kessler et al, 2010;Nielsen, 2016;Vaillant & Wolff, 2012). As already mentioned in Section 2, possibly due to data limitations, some studies in this literature also use parental health measures similar to ours (Alam, 2015;Bratti & Mendola, 2014;Frank & Meara, 2009;Mühlenweg et al, 2015).…”
Section: Measures Of Parental Healthmentioning
confidence: 99%